Investigation of Mineral-Aqueous Interfaces through Simulation and Scanning Probe Microscopy - Garcia, Natalya (Curtin University, 2020)
Crystallisation of calcium phosphate minerals is a complex process. Here several aspects of such systems have been studied - from mixed ion associates and prenucleation clusters to step edges of mineral surfaces - using a combination of computer simulation and atomic force microscopy. This has led to new insights into non-classical pathways for phosphate mineral formation.